2023
DOI: 10.1155/2023/5319266
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability and Microbial Ecology of Fresh Beef with Extremely Long Shelf-Life

Abstract: This study was aimed at assessing the pigment and lipid stability and characterising the microbial ecology by classical methods and metagenetics in beef with an extremely long shelf-life. Bovine longissimus thoracis et lumborum subprimals from different origins (Australia, Brazil, Ireland, and United Kingdom), displaying a shelf-life from 35 to 140 days in vacuum packaging, were aged at −1 (subzero storage) or a −1/+4°C two-level stepwise scheme. At different times, samples were repackaged under a high-oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…2). These findings corroborate the results of a previous study by Imazaki et al (2023), which demonstrated an inhibitory effect of the same C. maltaromaticum isolated strains on Enterobacteriaceae in beef stored in a low-oxygen atmosphere. The inhibition of this group of bacteria was also reported for Carnobacterium spp.…”
Section: Microbiological Countssupporting
confidence: 92%
See 3 more Smart Citations
“…2). These findings corroborate the results of a previous study by Imazaki et al (2023), which demonstrated an inhibitory effect of the same C. maltaromaticum isolated strains on Enterobacteriaceae in beef stored in a low-oxygen atmosphere. The inhibition of this group of bacteria was also reported for Carnobacterium spp.…”
Section: Microbiological Countssupporting
confidence: 92%
“…As noticed, C. maltaromaticum growth remained practically constant during storage and was barely affected by the inoculated or indigenous spoilage microbiota. The high population of Carnobacterium in these meat matrices is sustained by a previous study by Imazaki et al (2023), who isolated the C. maltaromaticum strains used in the present study from a long-term vacuum-packaged Australian beef, of which 98% of the final microbial composition was predominantly Carnobacterium. Other studies show that C. maltaromaticum can predominate over the spoilage population (Laursen et al, 2005) and persist in chilled meat until the end of the shelf-life (Holck, Pettersen, Moen, & Sørheim, 2014; Zhang, Badoni, Gänzle, & Yang, 2018).…”
Section: Microbiological Countssupporting
confidence: 60%
See 2 more Smart Citations